Cellular crosstalk in the bone marrow niche - Zeqi Huang; Zoya Iqbal; Zhe Zhao; Jianquan Liu; A. M. Alabsi; Maryam Shabbir; Ayesha Mahmood; Yujie Liang; Wencui Li; Zhiqin Deng (Journal of Translational Medicine)
Abstract The bone marrow niche is a special microenvironment that comprises elements, including hematopoietic stem cells, osteoblasts, and endothelial cells, and helps maintain their characteristic functions. Here, we elaborate on the crosstalk between various cellular components, hematopoietic stem cells, and other cells in the bone marrow niche. We further explain the mechanism of preserving equilibrium in the bone marrow niche, which is crucial for the directional regulation of bone reconstruction and repair. Additionally, we elucidate the intercommunication among osteocytes, the regulation of osteoblast maturation and activation by lymphocytes, the deficiency of megakaryocytes that can markedly impair osteoblast formation, and the mechanism of interaction between macrophages and mesenchymal stem cells in the bone marrow niche. Finally, we discussed the new immunotherapies for bone tumors in the BM niche. In this review, we aimed to provide a candid overview of the crosstalk among bone marrow niche cells and to highlight new concepts underlying the unknown mechanisms of hematopoiesis and bone reconstruction. Thus, this review may provide a more comprehensive understanding of the role of these niche cells in improving hematopoietic function and help identify their therapeutic potential for different diseases in the future. Graphical Abstract